PENAZAMAN HADIS TENTANG AL-QUR’AN (Kajian Kitab al-Masabih an-Nuraniyyah fi al-Ahadis al-Qur’aniyyah Karya KH Abdullah Umar)
; ">This article is trying to dwell upon a subject about an Indonesian opuswhich could be categorized into Koranic and Hadith Studies, that is alMaṣābiḥ al-Nūrāniyah f Naẓm al-Aḥādīs al-Qur’āniyyah, by K.H. Abdullah Umar al-Hafiz (1929-2001). He were a well-known muslim scholar in Koranic Studies particularly for Islamic Boarding School communities in Semarang. His effort in helping forward the education on Koranic studies were recognized in several regions in Indonesia as well as to the nearestneighboring countries. Al-Maṣābiḥ al-Nūrāniyah f Naẓm al-Aḥādīs alQur’āniyyah is unique, it comprises with poems of Prophet Muhammad’s hadiths that consist of all objects about Koran especially related to the position of Koran, the virtues of memorizing, and reading it. There are 53 palindromes of poem, each of 2 poems are a prelude which consist of approbation to Allah and invocation to the Prophet. While the rest of the book is the chapter “Fad